Conhecer para preservar: levantamento histórico-cultural e de patologias do Clube Ijuí – Ijuí/RS - Steinner, Hugo Henzel (2020)
This research focuses on urban buildings as spaces for conservation and preservation of social and cultural memories. Historical buildings occupy a prominent place both in the memory and in the past of cities, as well as in the contemporary imaginary by which cities are imagined, lived and shared. The research’ objective is to carry out a historical-cultural analysis and the constructive pathological manifestations found at Clube Ijuí, in the city of Ijuí, located in the northwest of the state of Rio Grande do Sul (Southern Brazil). The historical-cultural analysis is based on documentary research with different sources, using the history of the municipality and of the club, emphasizing issues related to cultural heritage and the preservation of historic buildings. The analysis of pathological manifestations is based on the damage map, a research and intervention methodology that allows the recognition of a plurality of elements that constitute the architectural, morphological and structural situation of buildings. This methodology identifies and evaluates problems and proposes solutions in order to conserve and preserve the urban heritage. As a result, this work presents an analysis focused on the building facades, describing the pathological manifestations found and the ideal treatment to be carried out to face it. In addition, the research warns of the importance of heritage preservation, especially of buildings of historical and architectural prestige, as a way of safeguarding local and regional culture.